Ilmu falak : perjumpaan khazanah Islam dan sains modern - Azhari, Susiknan, 1968- (Yogyakarta : Suara Muhammadiyah, 2004)
Astronomical calculations to determine qiblah, prayer times, and fasting based on Islamic calendar with a reference to Indonesia
Daftar pustaka : p. [177]-188
Keywords: Astronomy -- Religious aspects -- Islam; Calendar, Islamic